The Imagery of Interior Spaces - Bauer, Dominique; Kelly, Michael J. (punctum books, 2019)
On the unstable boundaries between "interior" and "exterior," "private" and "public," and always in some way relating to a "beyond," the imagery of interior space in literature reveals itself as an often disruptive code of subjectivity and of modernity. The wide variety of interior spaces elicited in literature - from the odd room over the womb, secluded parks, and train compartments, to the city as a world under a cloth - reveal a common defining feature: these interiors can all be analyzed as codes of a paradoxical, both assertive and fragile, subjectivity in its own unique time and history. They function as subtexts that define subjectivity, time, and history as profoundly ambiguous realities, on interchangeable existential, socio-political, and epistemological levels. This volume addresses the imagery of interior spaces in a number of iconic and also lesser known yet significant authors of European, North American, and Latin American literature of the nineteenth, twentieth, and twenty-first centuries: Djuna Barnes, Edmond de Goncourt, William Faulkner, Gabriel García Márquez, Benito Pérez Galdós, Elsa Morante, Robert Musil, Jules Romains, Peter Waterhouse, and Émile Zola.